DINAMIKA KEHIDUPAN BERSAMA MERTUA DALAM PERSEPEKTIF ISLAM - Arshya Oktaviana; Nur Awaliyah Asifa; Heni Ani Nuraeni (STKIP Subang, 2025)
Living with parents-in-law remains a common phenomenon in Indonesian society, influenced by economic factors, parents’ health conditions, and strong family-oriented cultural values. This multigenerational living arrangement creates complex family dynamics, particularly in the relationship between married couples and parents-in-law, and may lead to potential conflicts arising from differences in habits, lifestyles, values, and generational perspectives. This article aims to examine the dynamics of living with parents-in-law from the perspective of Islamic muamalah to understand how Islamic values are applied in maintaining family harmony. This study employs a qualitative approach through literature review and analysis of interview findings. The results indicate that Islamic muamalah principles—such as ta’awun (mutual assistance), ihsan (benevolence), syura (deliberation), as well as the observance of proper conduct and respect for privacy—play a significant role in fostering harmonious, respectful, and just relationships within extended families. Effective communication, cooperation between spouses, and adaptability are identified as key factors in managing these dynamics. While living with parents-in-law requires tolerance and mutual understanding, the independence of the nuclear family should still be pursued as a form of balance between fulfilling responsibilities toward parents and developing one’s own household. Therefore, the application of Islamic muamalah values serves as an essential foundation for maintaining harmony in multigenerational family life.